2018
DOI: 10.3390/rs10060863
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Lidars for Wind Turbine Control Applications—Results from the IEA Wind Task 32 Workshop

Abstract: IEA Wind Task 32 serves as an international platform for the research community and industry to identify and mitigate barriers to the use of lidars in wind energy applications. The workshop "Optimizing Lidar Design for Wind Energy Applications" was held in July 2016 to identify lidar system properties that are desirable for wind turbine control applications and help foster the widespread application of lidar-assisted control (LAC). One of the main barriers this workshop aimed to address is the multidisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 41 publications
2
66
0
Order By: Relevance
“…[14][15][16][17][18][19][20] The feasibility of proactive wind turbine control has been primarily examined using nacelle-mounted look-ahead technologies (eg, lidar), which typically measure the near-upstream portion of the wind field. 16,[19][20][21][22][23] The inflow forecasts were constructed upwards of 60 seconds in advance at one-second time intervals. These high-fidelity turbine inflow previews are generated from the DD wind maps using advection knowledge provided by the spatial correlation technique.…”
Section: Methodology To Produce Long Lead Wind Turbine Inflow Forecmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] The feasibility of proactive wind turbine control has been primarily examined using nacelle-mounted look-ahead technologies (eg, lidar), which typically measure the near-upstream portion of the wind field. 16,[19][20][21][22][23] The inflow forecasts were constructed upwards of 60 seconds in advance at one-second time intervals. These high-fidelity turbine inflow previews are generated from the DD wind maps using advection knowledge provided by the spatial correlation technique.…”
Section: Methodology To Produce Long Lead Wind Turbine Inflow Forecmentioning
confidence: 99%
“…Potential wind plant proactive control benefits include improvements to power output and a reduction in wind turbine loads . The feasibility of proactive wind turbine control has been primarily examined using nacelle‐mounted look‐ahead technologies (eg, lidar), which typically measure the near‐upstream portion of the wind field . The extent of the upstream wind field measurement inherently limits the preview time available to turbines to enact proactive wind turbine control strategies.…”
Section: Applications and Validationmentioning
confidence: 99%
“…This bounds the usability of single lidars to offshore sites (Peña et al, 2008) and sites with simple topography onshore . Therefore, when the flow is complex, as it is the case in more than 50 % of the onshore sites (e.g., hilly terrain) with good wind resources (Bingöl, 2010), multi-lidar instruments, such as long-range (Vasiljević et al, 2016) or short-range (Sjöholm et al, 2014) WindScanner systems, are needed to accurately retrieve the full wind flow. This of course drastically increases costs (several lidars) as well the complexity of measurements (installation, configuration, synchronization and monitoring) and corresponding data analysis (processing and integrating several datasets).…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbine control is widely used in the wind energy industry to ensure long structural life and efficient performance of wind turbines operating under complex environmental conditions [130]. In recent decades, Doppler LiDAR technique has received considerable interest in the possibility of improving wind turbine control by providing look-ahead wind measurements in front of the rotor plane [131].…”
Section: Turbine Controlmentioning
confidence: 99%
“…In addition, the torque control strategy led to a dramatic increase in loads on the shaft [140]. Experimental and numerical studies indicated that yaw control and pitch control could benefit from wind fields obtained from LiDAR measurements [131]. Fleming et al [135] estimated an increase of 2.4% in annual energy production if LiDAR data was used to correct wind vane measurements in yaw control.…”
Section: Turbine Controlmentioning
confidence: 99%